2022
DOI: 10.1253/circrep.cr-22-0050
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Trends and Changes in the Pre- and In-Hospital Medical Management of Acute Myocardial Infarction During the First 12 Months of the COVID-19 Pandemic in Mie Prefecture ― Report From the Mie ACS Registry ―

Abstract: prefectures, and was expanded to the entire nation, including Mie prefecture, on April 16, 2020. This led to behavioral changes in patients and affected access to medical facilities. 2,3 S ince late 2019, COVID-19 has spread worldwide. 1The World Health Organization declared COVID-19 a pandemic on March 11, 2020 and lockdowns were implemented in several major cities around the world to control infection.In Japan, the first case of COVID-19 was confirmed in the middle of January 2020. The first case of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Under the COVID‐19 pandemic, several studies in Japan reported that the time for prehospital care increased for patients with out‐of‐hospital cardiac arrest, acute myocardial infarction, and stroke. 23 , 24 , 25 However, a study dealing with the victims of traffic accidents in the early stage of the COVID‐19 pandemic found no change in the time for prehospital care. 3 In the present study dealing with major trauma, the time for prehospital care increased significantly in 2020 compared to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Under the COVID‐19 pandemic, several studies in Japan reported that the time for prehospital care increased for patients with out‐of‐hospital cardiac arrest, acute myocardial infarction, and stroke. 23 , 24 , 25 However, a study dealing with the victims of traffic accidents in the early stage of the COVID‐19 pandemic found no change in the time for prehospital care. 3 In the present study dealing with major trauma, the time for prehospital care increased significantly in 2020 compared to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that in-hospital mortality during the pandemic was worse than during the pre-pandemic period [ 1 ]. Factors contributing to this trend include delayed time from symptom onset to treatment due to individual hesitation to visit hospitals for fear of contracting COVID-19, delays in transportation, and wait time for the results of COVID-19 screening tests [ 1 , 20 ]. In Japan, an increase in the proportion of mechanical complications in patients with STEMI with delayed reperfusion due to delayed hospital arrival during the pandemic has been reported [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a single-center study in Tokyo reported that the 30-day cumulative mortality of STEMI patients during the COVID-19 pandemic was higher than that during the pre-pandemic period; however, the difference was not significant (13.7% of 117 patients vs. 6.6% of 281 patients, P = 0.074) [ 30 ]. In Mie Prefecture, Japan, the in-hospital mortality of patients with AMI during the early phase of the pandemic (April 2020 to September 2020) was not significantly different from that during the pre-pandemic period [ 20 ].…”
Section: Discussionmentioning
confidence: 99%